2014
DOI: 10.1177/0278364914543671
|View full text |Cite
|
Sign up to set email alerts
|

Tissue removal inside the beating heart using a robotically delivered metal MEMS tool

Abstract: A novel robotic tool is proposed to enable the surgical removal of tissue from inside the beating heart. The tool is manufactured using a unique metal MEMS process that provides the means to fabricate fully assembled devices that incorporate micron-scale features in a millimeter scale tool. The tool is integrated with a steerable curved concentric tube robot that can enter the heart percutaneously through peripheral vessels. Incorporating both irrigation and aspiration, the tissue removal system is capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Otherwise, owing to high compliance and bio-compatibility with non-energized parts, they are excellent candidates for various medical applications such as miniaturized surgical manipulators 36,44,45,73,135 , catheters 11,79 , graspers 173 , positioning system 166 , tissue removal tool 205 , fluidic actuator for neurosurgical instrument 138 , and hydraulic hood for ESD 134 . Based on the review of applications, the dimension of fluidic actuators is also various, ranging from 0.9mm (Catheter 79 ) to 35mm (TIFF-FLOP 36 ) (see the table 2 for more details).…”
Section: B Fluidic Actuatormentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, owing to high compliance and bio-compatibility with non-energized parts, they are excellent candidates for various medical applications such as miniaturized surgical manipulators 36,44,45,73,135 , catheters 11,79 , graspers 173 , positioning system 166 , tissue removal tool 205 , fluidic actuator for neurosurgical instrument 138 , and hydraulic hood for ESD 134 . Based on the review of applications, the dimension of fluidic actuators is also various, ranging from 0.9mm (Catheter 79 ) to 35mm (TIFF-FLOP 36 ) (see the table 2 for more details).…”
Section: B Fluidic Actuatormentioning
confidence: 99%
“…The ESD procedure was successfully carried out in a porcine stomach and the results demonstrated that the hood is able to generate enough force (1005 mN) to lift up the lesion and expand the view of submucosa. One of the state-of-the-art for surgical tools using fluidic actuation is the tissue removal device designed by Vasilyev et al, 205 from Harvard Medical School, USA. This tool is attached and intergraded to a steerable concentric tube robot that can be inserted into the beating heart via peripheral vessels.…”
Section: Conceptual Designmentioning
confidence: 99%
“…Consequently, published results on beating heart tissue removal have been limited to creation of an atrial septal defect consisting of a hole between the right and left atria [14]. This procedure did not require precise depth control since the goal was penetration of the tissue layer.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical curve model based on the constant curvature assumption was reported for four-way tendon driven catheter position control (Camarillo et al, 2008). In Vasilyev et al (2015), a new device to remove target tissue in the heart has been reported. The device was attached at end of the concentric tube manipulator and was positioned using a forward kinematic model.…”
mentioning
confidence: 99%
“…Accounting for these above mentioned physical phenomena can result in a high level of complexity in a modelbased control approach. To address the previously mentioned model limitations Eppinger and Seering (1987), Chiaverini et al (1999), Camarillo et al (2008), Patronik et al (2009), Kesner and Howe (2011), Samuel and Robert (2011), and Vasilyev et al (2015, we develop a model-free catheter tip position control. The model-free controller is implemented on a new robotic catheter steering system for autonomous catheter position control.…”
mentioning
confidence: 99%